Neurturin regulates the lung-resident macrophage inflammatory response to viral infection - Connolly, Emma (Life Sci Alliance, 2020)
Lung-resident macrophages are crucial to the maintenance of health and in the defence against lower respiratory tract infections. Macrophages adapt to local environmental cues that drive their appropriate function; however, this is often dysregulated in many inflammatory lung pathologies. In mucosal tissues, neuro-immune interactions enable quick and efficient inflammatory responses to pathogenic threats. Although a number of factors that influence the antimicrobial response of lung macrophages are known, the role of neuronal factors is less well understood. Here, we show an intricate circuit involving the neurotrophic factor, neurturin (NRTN) on human lung macrophages that dampens pro-inflammatory cytokine release and modulates the type of matrix metalloproteinases produced in response to viral stimuli. This circuit involves type 1 interferon–induced up-regulation of RET that when combined with the glial cell line-derived neurotrophic factor (GDNF) receptor α2 (GFRα2) allows binding to epithelial-derived NRTN. Our research highlights a non-neuronal immunomodulatory role for NRTN and a novel process leading to a specific antimicrobial immune response by human lung-resident macrophages.